Pipefish or Pipe Dream? - LeBlond, Paul H.; Bousfield, Ed L. (Journal of Scientific Exploration, 2011)
This Letter is a reply to the research article “A Baby Sea-Serpent No More: Reinterpreting Hagelund’s Juvenile ‘Cadborosaur’ Report,” in JSE 25:3, Fall 2011 (Woodley, Naish, & McCormick, 2011). Naish and colleagues indulge in the common home-quarterbacking habit of insisting that anything described as different must be an erroneous description of something found in a book that vaguely looks like it. A comparison of Hagelund’s “baby-Caddy” with a pipefish (Figure 1) shows significant differences in the latter.